Persepsi dan Kecemasan Mahasiswa D3 Keperawatan dalam Menghadapi Exam di Akper Kesdam 1/Bukit Barisan Pematangsiantar - Anita Yunia, Eva (Civiliza Publishing, 2023)
This research aims to analyze the perceptions and anxiety of D3 Nursing students in facing exams at Akper Kesdam 1/Bukit Barisan Pematangsiantar. The design of this research is a type of analytical descriptive research that has a cross sectional approach. moderate perception related to the exit exam, while the majority of them, as much as 48.7%, experienced moderate levels of anxiety when facing the exam. The research results also show that there is a significant relationship between students' perceptions about leaving the exam and their level of anxiety when facing the exam, with a p value of 0.000 which is less than 0.05. In addition, the strength of the relationship between the two variables is considered strong, with a correlation coefficient of 0.708.